Percepções de professoras da educação infantil sobre sua própria escrita: elaboração de uma proposta formativa docente para o aprimoramento da produção de textos no contexto escolar/profissional - Esteves, Sandra Regina Ferreira (2023)
The act of writing an essay is not a task that you can achieve solely by codifying ideas through graphic symbols. During the writing process, we should consider the many stages involved in it. From the planning phase, through the actual writing, to the subsequent moments of revision and rewriting. In this research, we intend to analyze the perceptions of a group of teachers from Early Childhood Education at a specific municipal Center for Early Childhood Education (CEMEI) located in São Carlos/SP, regarding their own writing, considering the essays they produce during their professional teaching routine. This way, we intend to identify and understand what these professionals comprehend about the writing process so we can elaborate a training proposal in order to enhance text in the professional school context. To this end, we rely on the ideas of authors who discuss the meaning of text, discourse and what textual/discursive genres are (BAKHTIN, 1997; ROJO, 2005; MARCUSHI, 2008; ANTUNES, 2017), the stages of writing (ANTUNES, 2003; DOLZ; GAGNON; DECANDIO, 2010; TRAVAGLIA, 2016), also, in order to create a contextualized teaching methodology, the role of the teachers formatives proposals (NÓVOA, 1992; CANDAU, 1997; IMBERNÓN, 2006). This is a qualitative research, like a case study, based on questionnaires answered by 15(fifteen) teachers and document analyzes from reports by these same professionals, one essay written by each teacher. By openly debating the art of writing, the beliefs surrounding the comprehension regarding the act of writing and the procedures essentials to the teacher’s writing, we hope to contribute to the shaping of thoughtful teachers, allowing them to critically analyze their actions and teaching practices. The technical-technological product resulting from this study is the elaborated teacher training proposal.